Allogeneic hematopoietic stem cell transplantation for adult acute lymphoblastic leukemia: Results from a single center, 1993-2011 - Yönal Hindilerden, İpek; Kalayoğlu Beşışık, Sevgi F.; Gürses-Koç, Nuray; Hindilerden, Fehmi; Sargın, Deniz (Tehran University of Medical Sciences (TUMS), 2017)
Background: For adult ALL patients, the indications and appropriate timing of allogeneic hematopoietic stem cell transplantation (AHSCT) continue to be debated. The primary aim of this single-institution study was to compare the results of our adult ALL patients that had been allografted with those reported in the current literature. Subjects and Methods: This study included 53 consecutive adults with acute lymphoblastic leukemia (ALL) who underwent allogeneic hematopoietic stem cell transplantation (AHSCT) with myeloablative (92%) and reduced-intensity (8%) conditioning between 1993 and 2011. Results: Mean patient age was 27 years (SD: 8.62) and donor age was 33.7 years (SD: 9.47). Fourteen patients were in first remission; 21 in ?2nd remission, 15 in relapse and 3 had primary refractory leukemia. Thirty-four, 15 and 4 patients received busulfan plus cyclophosphamide, cyclophosphamide/total body irradiation and fludarabine-based regimens, respectively. For graft-versus-host disease (GVHD) prophylaxis, cyclosporine plus methotrexate were used. Forty-six donors were related and 7 were unrelated. Thirty patients received granulocyte-colony stimulating factor (G-CSF) mobilized peripheral blood and 23 received bone marrow as stem cell source. Twenty-six patients relapsed at a mean duration of 11.3 months (SD: 19.1). Forty-four patients succumbed to their disease after a mean follow-up of 13.6 months (SD: 19.5). The cause of mortality was relapse (n=24; 54.5%) and transplant-related etiologies (n=20; 45.5%). The estimated five year probabilities of overall survival (OS) and progression-free survival (PFS) were 37% and 12%, respectively. Conclusion: By multivariate analyses, transplantation in first remission was the most important predictor of transplant success.
Keywords: Acute Lymphoblastic Leukemia; Allogeneic Hematopoietic Stem Cell Transplantation; Overall Survival; Progression-Free Survival